Telerehabilitation in the high southern latitude. Results of a treatment implementation for people with disabilities during the COVID-19 pandemic Telerehabilitación en alta latitud sur. Resultados de una implementación de tratamiento para personas en situación de discapacidad durante la pandemia de COVID-19 - Andrade Gallardo, A.; Rogosich Cvitanic, V.; Barría Aburto, P.; Henriquez Diaz, H.; Aguilar Cardenas, Rolando Nemecio; Nuñez Espinosa, Cristian Andrés (My University, 2022)
The health situation after the emergence of COVID-19 has precipitated the use of new technologies and the adaptation of rehabilitation services of all kinds. Objective: To describe the implementation of a telerehabilitation system in patients with different diagnoses of disability living in the high southern latitude during the COVID-19 pandemic. Methods: A system of personalized therapies guided by videoconference was implemented for patients with varying diagnoses of disability. The patients were grouped into three age groups (Minors; Adults; Older Adults) and six types of clinical diagnosis (conditions originating in the perinatal period, diseases of the circulatory system, diseases of the nervous system, diseases of the musculoskeletal system, and connective tissue, mental and behavioural treatments and other diagnoses). The patient's diagnosis, the type of care required, the number of sessions, and the level of satisfaction of each user were evaluated based on the telerehabilitation they received. Results: 101 patients with an average age of 31 ± 26 years participated, 52.5% were male. All of them managed to handle the minimum technologies required for telerehabilitation care. There is a degree of association between the patient's diagnosis and the age group (p <.05), as well as between the diagnosis and the type of care required (p <.05). After implementation, users positively evaluated distance therapy. Conclusions: Telerehabilitation can be implemented in patients with disabilities in areas of high southern latitude, respecting the different stages of the process, to ensure it is correctly delivered.
Keywords: covid-19; disabled persons; high southern latitude; telerehabilitation